Безпровідна система моніторингу деформацій з використанням тензорезисторів на основі ниткоподібних кристалів кремнію - Druzhinin, Anatoliy; Koretskyi, Roman; Nichkalo, Stepan; Talanchuk, Danylo (Технологія та конструювання в електронній апаратурі, 2025)
Structural health monitoring of steel pipelines in industrial environments remains a critical challenge due to mechanical loads, pressure variations, temperature fluctuations, and external degradation. Traditional foil strain gauges, though widely used and inexpensive, suffer from thermal instability, limited operational life under cyclic loading, and the need for hermetic protection, restricting their application in infrastructure monitoring. Optical fiber sensors offer high precision, but are costly and difficult to integrate. This paper presents a wireless deformation monitoring system based on silicon whiskers used as strain-sensitive elements embedded into a Wheatstone bridge. One of the bridge’s four arms includes a silicon whisker sensor, while the others use 350 Ω precision tantalum resistors, ensuring thermal stability. The analogue output of the bridge is amplified and digitized by an HX711 ADC and processed by an Arduino-compatible microcontroller, which transmits the data via Wi-Fi. For thermal compensation, a “bridge within a bridge” configuration is used, allowing real-time correction of temperature-induced drift.Experimental validation was carried out on a water pipeline segment under simulated pressures of up to 12 bar. The silicon whisker-based sensors demonstrated a stable gauge factor of ~120 ± 10% and a thermal resistance drift within +(0.1 ± 0.02)%/°C over the temperature range from −150 to +200 °C. The system reliably measured strain up to ±5ꞏ10⁻³ (0.5%), matching expected deformations in steel pipeline applications. The results of the extended temperature test showed that when heated to +350°C, the measurement error caused by the temperature coefficient of resistance does not exceed 1.2% after digital correction. Therefore, for the practical system, a “bridge-in-a-bridge” thermal compensation scheme was used, where one of the arms acts as a reference thermal control link.The proposed system offers a compact solution for real-time strain monitoring in industrial settings. Its wireless functionality, thermal resilience, and measurement precision make it highly suitable for continuous diagnostics and early fault detection.